O-008 Aberrant Anti-inflammatory Macrophage Function and Differentiation in Wiskott-Aldrich Syndrome Protein-Deficient Mice and Humans. (March 2016) - Biswas, Amlan; Shouval, Dror; Goettel, Jeremy; Field, Michael; Griffith, Alexandra; Pai, Sung-Yun; Notarangelo, Luigi; Geha, Raif; Snapper, Scott
Abstract : Background: The intestinal mucosal surface is continuously exposed to microbial communities and intestinal homeostasis is dependent on host barrier function and the establishment and persistence of well-regulated immune responses. Innate immune cells play a critical role in the maintenance of mucosal homeostasis by facilitating immune tolerance to luminal antigens. A recent study identified an inflammatory bowel disease (IBD) causal sub-network of genes (e.g., IL10, ARC, NOD2, HCK, WAS), which were highly enriched in bone marrow derived macrophages (Mφ) and predicted to have a role in anti-inflammatory macrophage function. The Wiskott-Aldrich syndrome (WAS) gene was identified within this causal sub-network along with HCK, a protein that interacts with Wiskott-Aldrich syndrome protein (WASP). WASP-deficient mice and up to 10% of WAS patients develop IBD. We have shown that WASP-deficiency in mice, when limited to innate immune cells, is sufficient to render normal wild-type CD4 + T cells colitogenic. We hypothesized that WASP-mediated regulation of anti-inflammatory Mφ function is critical for the maintenance of intestinal homeostasis. Methods: We analyzed the expression of Ly6c and MHCII in mucosal macrophages (CD45 + CD11b + CD11c − CD64 + CD103 − ) to distinguish them into pro- and anti-inflammatory Mφ populations. Bone marrow derived Mφ (BMDM) in mice and monocyte derived Mφ in human was polarized into anti-inflammatory M2 Mφ in presence of IL4, TGFb and IL10. Results: Analysis of gut resident Mφ population in 5-weeks-old pre-colitic Was −/− mice showed an increase in the percentage of pro-inflammatory Mφ (Ly6c high MHCII high ) and a concomitant decrease in the percentage of anti-inflammatory Mφ (Ly6c low MHCII high ). As predicted, in a bone-marrow chimera experiment, where lethally irradiated Was −/− mice were transferred with a mixture of WT (CD45.1) and Was −/− (CD45.2) bone-marrow in a 1:1 ratio, the Was −/− compartment, harbored an increased percentage of pro-inflammatory Mφ and decreased anti-inflammatory Mφ compared to the WT compartment. Next we examined the role of Mφ–intrinsic WASP in intestinal homeostasis by transferring CD4 + T cell into Rag1 −/− mice lacking WASP only in Mφ (Rag1 −/− Was fl/fl LysM Cre ). Rag1 −/− Was fl/fl LysM Cre recipient mice, when compared to Rag1 −/− mice, developed more severe weight loss and colonic inflammation with increased pro-inflammatory cytokine expression. In addition, in vitro generation of BMDM M2 Mφ from Was −/− mice expressing classical M2 markers Arg1 and Fizz1, was also markedly reduced when compared with M2 Mφ derived from WT mice. LPS induced a much higher expression of pro-inflammatory cytokines in Was −/− M2 Mφ compared to WT M2 Mφ. Moreover, Was −/− M2 Mφ induced greater proliferation of CD4 + T cells, cytokine production, and decreased generation of Tregs compared to WT Mφ. Importantly, the colitis that results from the transfer of CD4 + T cells into Rag1 −/− Was −/− mice was rescued by the transfer of WT M2 Mφ but not Was −/− M2 Mφ. Similarly, we found that the M2 Mφ generation was also severely impaired in patients with Wiskott-Aldrich syndrome. M2 Mφ from patients expressed higher levels of pro-inflammatory cytokines and was less efficient in the generation Tregs in an in vitro co-culture system. Conclusions: Collectively, these data implicates a critical Mφ-intrinsic functional role for WASP for the generation and maintenance of tolerance in the intestinal mucosa.